A State-of-The-Art Technical Review on Seismic Resilience of Rcc Structural Components Using Seismic Resistance Based Retrofitting Techniques - Shah, Rinky; K.C, Sanjay; Bhagat, Shubhanshu Kumar; Chaudhary, Srijana; Pokharel, Subash; Yadav, Yogesh (Journal of Advanced College of Engineering and Management, 2023)
Existing buildings can be at a greater seismic risk due to non-conformance to current design codes and may require structural retrofitting to improve building performance. The most recent example of that can be seen from the 2015 AD earthquake in Nepal and other sub continental regions, where numbers of buildings were destroyed with more fatal consequences have drawn the attention of the government authorities of Nepal and the general public for seismic earthquake resistance design of buildings. Following the post seismic assessment of building in Nepal after 2015 earthquake, it is revealed that the existing reinforced concrete buildings have some inadequacies in structural components and thus the intensive research and study is required to for the better understanding of the structure in terms of immediate consequences due to direct damage and way to recovery using seismic retrofit assessment. This paper presents an overview on performance based evaluation of retrofitted rcc structural member using some advanced retrofitting techniques which is innovative and can be cost effective retrofitting strategies demanding less skilled man power. It is concluded that better seismic resilience can be achieved with the help of innovative methods with the application of innovative materials like textile mortars and fibers. In the following sections a review of experimental flexural loading on beam is presented.